Kontribusi Koordinasi Mata Tangan, Kekuatan Otot Lengan, dan Keseimbangan Terhadap Kemampuan Passing Bawah Pada Permainan Bola Voli - Ikadarny Ikadarny; Achmad Karim (Jendela Olahraga, 2020)
Contribution of Eye Hand Coordination, Arm Muscle Strength, and Balance Against the Ability to Passing Down in Volleyball GamesThis study aims to prove the contribution of eye hand coordination, arm muscle strength, and balance to the ability to pass under. The method in this research is correlation with the type of descriptive research. The number of students was 30 students with a simple random sampling method. Measurement of hand eye coordination is done by ball throwing test, measurement of arm strength by push up test, balance measurement by dynamic balance test, measurement of bottom passing by bouncing the ball up with a minimum limit of 2.30 meters. The results showed hand eye coordination, arm muscle strength, balance, and passing under normal distribution (p> 0.05) with the results of the correlation value (r> 0.05). Correlation test results of hand eye coordination to the ability of under passing (r = 0.73). Correlation test results of arm muscle strength to the ability of under passing (r = 0.76). Balance correlation test results with the ability to pass under (r = 0.74). The results of the double correlation test of hand eye coordination, arm muscle strength, and balance to the ability of under passing (r = 0.89). The conclusion of the study is that proven eye hand coordination, arm muscle strength, and balance contribute to the ability to pass under the game of volleyball. Extracurricular activities in schools are one of the important things to train and foster students as well as physical ability factors that can be used as a reference in selecting athlete seeds to be trained towards achievement. Keywords: eye hand coordination, arm muscle strength, balance, ability to pass under Penelitian ini bertujuan untuk membuktikan kontribusi koordinasi mata tangan, kekuatan otot lengan, dan keseimbangan terhadap kemampuan passing bawah. Metode dalam penelitian ini adalah korelasi dengan jenis penelitian deskriptif. Jumlah sampe sebanyak 30 siswa dengan metode pengambilan sampel simple random sampling. Pengukuran koordinasi mata tangan dilakukan dengan tes lempar tangkap bola, pengukuran kekuatan lengan dengan tes push up, pengukuran keseimbangan dengan tes keseimbangan dinamis, pengukuran passing bawah dengan cara melambungkan bola keatas dengan batas minimal 2,30 meter. Hasil penelitian menunjukkan koordinasi mata tangan, kekuatan otot lengan, keseimbangan, dan passing bawah terdistribusi normal (p>0,05) dengan hasil nilai korelasi (r>0,05). Hasil uji korelasi koordinasi mata tangan terhadap kemampuan passing bawah (r=0,73). Hasil uji korelasi kekuatan otot lengan terhadap kemampuan passing bawah (r=0,76). Hasil uji korelasi keseimbangan terhadap kemampuan passing bawah (r=0,74). Hasil uji korelasi ganda koordinasi mata tangan, kekuatan otot lengan, dan keseimbangan terhadap kemampuan passing bawah (r=0,89). Kesimpulan dari penelitian adalah terbukti koordinasi mata tangan, kekuatan otot lengan, dan keseimbangan berkontribusi terhadap kemampuan passing bawah pada permainan bola voli. Kegiatan ekstrakulikuler di sekolah merupakan salah satu hal penting untuk melatih dan membina siswa serta faktor kemampuan fisik yang dapat dijadikan acuan dalam memilih bibit atlet untuk dilatih ke arah pencapaian prestasi.Kata Kunci: koordinasi mata tangan, kekuatan otot lengan, keseimbangan, passing bawah